In full retreat: the Canadian government's new environmental assessment law undoes decades of progress - Gibson, Robert B. (Impact Assessment and Project Appraisal, 2012)
The Canadian Environmental Assessment Act 2012, which came into force on 6 July 2012, virtually eliminates the core of federal-level environmental assessment in Canada. Under the new law, federal environmental assessments will be few, fragmentary, inconsistent and late. Key decision-making will be discretionary and consequently unpredictable. Much of it will be cloaked in secrecy. The residual potential for effective, efficient and fair assessments will depend heavily on requirements under other federal legislation and on the uneven diversity of provincial, territorial and Aboriginal assessment processes. This paper reviews the key characteristics of the new law in light of 10 basic design principles for environmental assessment processes, and considers the broader international implications of the Canadian retreat from application of these principles.